ENANAMAN NILAI AGAMA ISLAM TERHADAP SISWA DI SDN 3 DOLO (Tinjauan dari Segi Interaksi Edukatif) - Firdiansyah Alhabsyi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2020)
Efforts to Increase the Inculcation of Islamic Religious Value of Students in SDN 3 Dolo (Overview of the terms ofEducational Interaction) are generally carried out in various ways, both through schools and from private teachers ofIslamic religious education. This is manifested through: (1) Routine Teaching Routine Reading short surah of theQur'an; (2) Memorization of short verses of the Qur'an; and (3) Media usage.By increasing the inculcation of Islamic religious values towards students, there are several obstacles, such as thedifferent levels of understanding of each student, which are specifically found in the process of memorizing short surasof the Qur'an. The difference in the level of understanding in absorbing lessons that occur in students is caused bystudents' different educational backgrounds. Because not all students who come from Kindergarten (Kindergarten)education are based on religion so that in the field of reading Iqra 'or memorizing al-Qur'an' also the level is alsodifferent. As a solution to overcome these problems, teachers, especially Islamic Education Subject Teachers, have theappropriate techniques to overcome these problems, for example by holding Les Sore (Supplementary Lessons).